KINERJA PEGAWAI RUMAH SAKIT UMUM DAERAH BENGKALIS (STUDI KASUS PELAYANAN PASIEN YANG DIRUJUK KE RSUD ARIFIN AHMAD PEKANBARU) - Muhammad Aryan Maulana; Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research present describe about quality of staff in Bengkalis Hospital (study case service of patient to Arifin Ahmad Hospital Pekanabru). Hospital are public place for in healthy. Hospital in Bengkalis have a B type and now service of patient in Bengkalis Hospital cannot optimally because the increase of disease in society. The hospital that have a type A in Pekanbaru are Arifin Ahmad Hospital.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Bengkalis Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes docter specialist, docter, patient and nurse in Bengkalis Hospital.The conclusion of this research are the quality of staff in Hospital (study case service of patient to Arifin Ahmad Hospital Pekanabru) are held base on standart operational procedure likes quality of staff, time services, and the paid for patient. And factors that influence the quality of staff in Bengkalis Hospital are communication between staff, human resources and medical tools that the Bengkalis Hospital mines.Keywords: quality, staff, hospital and service.